Elevated dietary selenium rescues mitochondrial capacity impairment induced by decreased vitamin E intake in young exercising horses. (1st August 2022) - Owen, Randi N; Semanchik, Pier L; Latham, Christine M; Brennan, Kristen M; White-Springer, Sarah H
Abstract: Maintenance of mitochondrial health, which is supported in part by dietary antioxidants such as selenium (Se) and vitamin E (vitE), is pertinent to optimizing athletic performance. Deficiencies in Se and vitE negatively impact muscle health but mitochondrial adaptations to various levels of dietary Se and vitE are poorly understood. Young Quarter Horses (mean ± SD: 17.6 ± 0.9 mo) undergoing submaximal exercise training were used to test the hypothesis that a proprietary antioxidant blend containing elevated Se yeast (EconomasE, Alltech, Inc., Nicholasville, KY) would improve mitochondrial characteristics compared to Se at current requirements, even with reduced vitE intake. Horses were balanced by age, sex, body weight (BW), and farm of origin and randomly assigned to one of three custom-formulated concentrates fed at 1% BW (dry matter, DM basis) for 12 wk: 1) 100 IU vitE/kg DM and 0.1 mg Se/kg DM (CON, n = 6); 2) no added vitE plus EconomasE to provide 0.1 mg Se/kg DM (ESe1, n = 6); or 3) no added vitE plus EconomasE to provide 0.3 mg Se/kg DM (ESe3, n = 6). Samples collected at week 0 and 12 were analyzed for serum Se and middle gluteal glutathione peroxidase (GPx) and mitochondrial enzyme activities by kinetic colorimetry and mitochondrial capacities by high-resolution respirometry. Data were analyzed using mixed linear models in SAS v9.4 with repeated measures (time) and fixed effects of time, diet, and time × diet; horse(diet) served as a random effect. Serum Se tended to increase in all horses by week 12 ( P = 0.08) but was unaffected by diet. Muscle GPx activity remained similar among all horses throughout the duration of the study. Mitochondrial volume density (citrate synthase [CS] activity), integrative function (cytochrome c oxidase [CCO] activity per mg protein), and integrative (per mg tissue) oxidative (P) and electron transfer (E) capacities increased from week 0 to 12 in all horses ( P ≤ 0.01). Intrinsic (relative to CS) CCO activity decreased in all horses ( P = 0.001), while intrinsic P and E capacities decreased only in ESe1 horses from week 0 to 12 ( P ≤ 0.002). These results suggest that feeding EconomasE to provide 0.3 mg Se/kg DM may prevent adverse effects of removing 100 IU dietary vitE/kg DM on mitochondria in young horses. More research is needed to determine optimal dietary Se and vitE levels in performance horses to maximize mitochondrial energy production. Lay Summary: Mitochondria, colloquially referred to as the powerhouses of the cell, are essential for sustained energy production, which is particularly important for athletic performance. During exercise, reactive oxygen species (ROS) are produced as a normal byproduct of muscle contraction. ROS act as critical signaling molecules and are essential to stimulate adaptation to exercise and other stressors. However, if excess ROS are produced and not sequestered by antioxidants, they may damage cellular components such as lipids, proteins, and DNA. Selenium (Se) and vitamin E (vitE) are two primary dietary antioxidants that aid in quenching excess ROS. To evaluate the impact of Se and vitE on mitochondria, three diets differing in Se and vitE levels were provided to lightly exercising young horses for 12 wk. Skeletal muscle mitochondrial capacity was negatively impacted by the reduction of dietary vitE, which was rescued with elevated dietary Se. The results highlight the importance of determining optimal levels of minerals and vitamins in performance horse diets to ensure proper energy production during exercise. Abstract : Dietary selenium provided at 0.3 mg/kg dry matter offsets mitochondrial deficits induced by reduced vitamin E intake. Optimal dietary vitamin and mineral requirements must be determined to ensure prevention of fatigue in performance horses.